Dilemmas concerning the use of polygraph-technology in the judicial process (Academic Journal of Internal Affairs, 2013)
The author provides an overview of the debate that concerns the judicial acceptance of evidence extracted by polygraph technology during the investigation process.
Keywords: polygraph; testing; regulation